Menyongsong Merdeka Belajar: Implementasi Konsep Kampus Merdeka Di Perguruan Tinggi - Lasino Lasino (Pusat Riset dan Inovasi Nasional, 2021)
Higher education in Indonesia is currently facing big challenges in adapting to the needs of an ever-evolving era. The concepts of